Solution and rheological properties of polyacrylamide in 1, 4-dioxane + water mixed solvent media. Issue 9 (1st September 2020) - Debnath, Bidyut; Chakraborty, Gulmi; Saha, Swapan K
Abstract: The hydrodynamic properties of uncharged polymers of acrylamide has been investigated in 1, 4-dioxane (DO) + water mixed solvent media at 303 K, 313 K and 323 K temperatures as probed by viscometry to explore the dimension and conformation of individual polymer molecules. In this study three different average molar masses of PAM, e.g., 8.9 × 10 6 (designated as Type-A), 1.6 × 10 6 (designated as Type-B), and 2.3 × 10 5 (designated as Type-C) g·mol −1 were employed. The unperturbed dimensions ( K θ ) under non-theta condition of polymer molecules has been determined for various solvent compositions clearly indicates that though DO acts as poor solvent in our system but some compositions of solvent acts as a good solvent. The temperature coefficient of unperturbed dimension ( d ln ( r 0 2 ) / d T) has been found negative for polyacrylamide in the mixed solvent systems indicating a weak helical nature. Rheological stress sweep measurements of Type-A PAM solutions at 298 K reveal marked increase in elasticity upon addition of DO in the mixed solvent compared to that in pure solvent. In the shear viscosity profile a significant increase in critical shear rate is observed with increase in temperature from 293 K to 298 K. The results are discussed in the light of microstructural arrangement of the PAM aggregates under different physiological conditions. Graphical Abstract: